2022
DOI: 10.3390/ijms23147837
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Platelet-Derived Extracellular Vesicles in Immune-Mediated Thrombosis

Abstract: Platelet-derived extracellular vesicles (PEVs) play important roles in hemostasis and thrombosis. There are three major types of PEVs described based on their size and characteristics, but newer types may continue to emerge owing to the ongoing improvement in the methodologies and terms used to define various types of EVs. As the literature on EVs is growing, there are continuing attempts to standardize protocols for EV isolation and reach consensus in the field. This review provides information on mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 222 publications
0
8
0
Order By: Relevance
“…In physiological states, CTS-EVs secreted from blood cells, especially platelet-derived EVs, have garnered considerable scientific interest. Their abundance in the bloodstream and pivotal roles in processes such as wound healing, angiogenesis, thrombosis, and atherosclerosis make them a significant focus of study [ 201 , 202 , 203 , 204 ]. The isolation of these EVs, which requires further study, could aid the understanding and treatment of a variety of clotting disorders and thrombocytopenias [ 205 ].…”
Section: Cts-evs In Physiology and Pathologymentioning
confidence: 99%
“…In physiological states, CTS-EVs secreted from blood cells, especially platelet-derived EVs, have garnered considerable scientific interest. Their abundance in the bloodstream and pivotal roles in processes such as wound healing, angiogenesis, thrombosis, and atherosclerosis make them a significant focus of study [ 201 , 202 , 203 , 204 ]. The isolation of these EVs, which requires further study, could aid the understanding and treatment of a variety of clotting disorders and thrombocytopenias [ 205 ].…”
Section: Cts-evs In Physiology and Pathologymentioning
confidence: 99%
“…Studies on the role of platelet EVs related to inflammation have been reported to increase their numbers in response to infection with viruses and parasites [ 221 ]. Platelet EVs orchestrate the immune response by modulating the performance of other immune cells [ 222 ]. Certainly, platelet EVs generated during inflammation [ 223 ] and acute liver injury and infiltrating into the bone marrow were essential for the regulation of megakaryocyte formation [ 224 ].…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%
“…The extent to which PEVs can increase thrombosis depends on both their number and composition. PEVs from pathologic conditions, such as disseminated intravascular coagulation (DIC), thrombocytopenia, and systemic lupus, are larger in diameter and richer in amount ( Ponomareva et al, 2017 ; Eustes and Dayal, 2022 ). Terrisse et al (2010) found that PEVs adhered to endothelial cells dependent on lactadherin, PS, and αVβ3 integrin.…”
Section: Platelet Extracellular Vesicles: Characterization Preparatio...mentioning
confidence: 99%